Household income exchange rates and farmer welfare in rice-farming communities: Evidence from Lampung Province, Indonesia - Indah, Lidya Sari Mas; Arifin, Bustanul; Ambya, Ambya (Privietlab, 2025)
The Household Farmer's Exchange Rate (NTPRP) is an indicator of farmer welfare in Indonesia. Farmers' purchasing power can be predicted through the NTPRP. The problem faced by farmers is low income, caused by farmers' expenditures on production inputs not being commensurate with their farm income. Furthermore, low income means that farmers' purchasing power for household consumption is insufficient to meet their basic needs. This study aims to analyze the income of farmer households, the level of farmer welfare with the NTPRP, and the determinants of farmer welfare. This study used a survey of 168 rice farmers in Lampung Province who were selected by random sampling. Lampung Province was chosen purposively as one of the fifth largest rice producers in Indonesia. The research was conducted from February to May 2025. This study used an analysis of farmer household income, cost analysis, and binary logit analysis. The results showed that the income of farmer households derived from rice on-farm contributed significantly to the household income of farmers, and the level of welfare based on the net total revenue to total cost of production of farmers in a less prosperous condition. The determinants of farmer welfare showed that rice farming income and off-farm income were positive and significant to farmer welfare, while food consumption expenditure was negative and significantly affected the welfare of rice farmer households in Lampung Province. The results of this study recommend that farmers diversify their income with the support of the agro-industry in rural areas, ease of access to modern technology, and the government needs to provide superior seeds, fertilizers, mini-mechanization, and sustainable intensification through farmer development and institutions.